2013
DOI: 10.1016/j.tcs.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Canadian traveler problem variants

Abstract: The Canadian traveler problem (CTP) is the problem of traversing a given graph, where some of the edges may be blocked -a state which is revealed only upon reaching an incident vertex. Originally stated by Papadimitriou and Yannakakis (1991), the adversarial version of CTP was shown to be PSPACE-complete, with the stochastic version shown to be #P-hard.We show that stochastic CTP is also PSPACE-complete: initially proving PSPACE-hardness for the dependent version of stochastic CTP, and proceeding with gadgets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 7 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Finally, we show that CTP in the scenario model on cactus graphs (graphs with the property that each edge is in at most one cycle) is also NP-hard. At this point, we would like to mention that the CTP in the scenario model has similar features with CTP with dependencies [10] and CTP with remote sensing [5,10]. In all these problems, it might be beneficial to explore the state of the graph before proceeding along a path.…”
Section: Scenario Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we show that CTP in the scenario model on cactus graphs (graphs with the property that each edge is in at most one cycle) is also NP-hard. At this point, we would like to mention that the CTP in the scenario model has similar features with CTP with dependencies [10] and CTP with remote sensing [5,10]. In all these problems, it might be beneficial to explore the state of the graph before proceeding along a path.…”
Section: Scenario Modelmentioning
confidence: 99%
“…They also showed that the problem is polynomially solvable if the number of scenarios is bounded by a constant. In the independent decision model, the decision version of CTP is PSPACE-complete [10] and it is #P-hard to compute the expected length [19,20]. It is even not possible to describe an optimal policy, unless PSPACE ⊆ P/poly [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bender and Westphal proposed a randomized algorithm for special graphs in which all s-t paths are vertex-disjoint [3]. There were also some recent work on the k-CTP for special graphs [4,5,24] and the variants of the k-CTP [11,25,29].…”
Section: Introductionmentioning
confidence: 99%
“…A crucial difference however with mean-payoff and other long-run properties is that, for long-run probabilities, the "weights" along a path are not fixed a priori, but do depend on the scheduler. In this aspect, there is some conceptual relation to dynamic Markov processes [34] where cost or transition probabilities depend on previously made decisions, or the stochastic variant of the Canadian traveler problem [25]. These problems, however, are concerned with finite-horizon objectives; moreover, their weights are affected by the past, whereas our "weights" (satisfaction probabilities) are induced by the future scheduler.…”
Section: Introductionmentioning
confidence: 99%